Muscle Free Fatty-Acid Uptake Associates to Mechanical Efficiency During Exercise in Humans - Laaksonen MS; Kyrolainen H; Kemppainen J; Knuuti J; Kalliokoski KK (FRONTIERS MEDIA SA, 2022)
Intrinsic factors related to muscle metabolism may explain the differences in mechanical efficiency (ME) during exercise. Therefore, this study aimed to investigate the relationship between muscle metabolism and ME. Totally 17 healthy recreationally active male participants were recruited and divided into efficient (EF; n = 8) and inefficient (IE; n = 9) groups, which were matched for age (mean +/- SD 24 +/- 2 vs. 23 +/- 2 years), BMI (23 +/- 1 vs. 23 +/- 2 kg m(-2)), physical activity levels (3.4 +/- 1.0 vs. 4.1 +/- 1.0 sessions/week), and (V)over dotO(2)peak (53 +/- 3 vs. 52 +/- 3 mL kg(-1) min(-1)), respectively, but differed for ME at 45% of (V)over dotO(2)peak intensity during submaximal bicycle ergometer test (EF 20.5 +/- 3.5 vs. IE 15.4 +/- 0.8%, P < 0.001). Using positron emission tomography, muscle blood flow (BF) and uptakes of oxygen (m(V)over dotO(2)), fatty acids (FAU) and glucose (GU) were measured during dynamic submaximal knee-extension exercise. Workload-normalized BF (EF 35 +/- 14 vs. IE 34 +/- 11 mL 100 g(-1) min(-1), P = 0.896), m(V)over dotO(2) (EF 4.1 +/- 1.2 vs. IE 3.9 +/- 1.2 mL 100 g(-1) min(-1), P = 0.808), and GU (EF 3.1 +/- 1.8 vs. IE 2.6 +/- 2.3 m mol 100 g(-1) min(-1), P = 0.641) as well as the delivery of oxygen, glucose, and FAU, as well as respiratory quotient were not different between the groups. However, FAU was significantly higher in EF than IE (3.1 +/- 1.7 vs. 1.7 +/- 0.6 m mol 100 g(-1) min(-1), P = 0.047) and it also correlated with ME (r = 0.56, P = 0.024) in the entire study group. EF group also demonstrated higher use of plasma FAU than IE, but no differences in use of plasma glucose and intramuscular energy sources were observed between the groups. These findings suggest that the effective use of plasma FAU is an important determinant of ME during exercise.